I'm trying a exercise from Peter Petersen's book, and I did the following:

Let $*$ be the Hodge star operator, I know that $\Lambda^2TM$ decompose into $+1$ and $-1$ eigenspaces $\Lambda^+TM$ and $\Lambda^-TM$ for $*$.

I know that, if $e_1,e_2,e_3,e_4$ is an oriented orthonormal basis, then $$e_1\wedge e_2\pm e_3\wedge e_4\in\Lambda^{\pm}TM$$ $$e_1\wedge e_3\pm e_4\wedge e_2\in\Lambda^{\pm}TM$$ $$e_1\wedge e_4\pm e_2\wedge e_3\in\Lambda^{\pm}TM$$

What i can't prove is:

Thus, any linear map $L:\Lambda^2TM\to\Lambda^2TM$ has a block decomposition $$\begin{bmatrix} A&B \\ C&D \end{bmatrix}$$

$$A:\Lambda^+TM\to\Lambda^+TM$$ $$B:\Lambda^-TM\to\Lambda^+TM$$ $$C:\Lambda^+TM\to\Lambda^-TM$$ $$D:\Lambda^-TM\to\Lambda^-TM$$


Presumably $M$ is a $4$-manifold here, since you are working with $\Lambda^2 TM$. If $M$ is $2n$-dimensional, the Hodge star gives rise to a decomposition $\Lambda^n TM = \Lambda^+ TM \oplus \Lambda^- TM$.

First, note that any $\omega \in \Lambda^2 TM$ can be written as $$\omega = \tfrac{1}{2}(\omega + \ast \omega) + \tfrac{1}{2}(\omega - \ast \omega) = \omega^+ + \omega^- \in \Lambda^+ TM \oplus \Lambda^- TM.$$ If $L: \Lambda^2 TM \longrightarrow \Lambda^2 TM$ is linear, we can once again write $$L(\omega) = L(\omega^+ + \omega^-) = L(\omega^+) + L(\omega^-).$$ But now both $L(\omega^+)$ and $L(\omega^-)$ can be decomposed with respect to the direct sum: $$L(\omega^+) = \tfrac{1}{2}(L(\omega^+) + \ast L(\omega^+)) + \tfrac{1}{2}(L(\omega^+) - \ast L(\omega^+)) = L(\omega^+)^+ + L(\omega^+)^-$$ and similarly $$L(\omega^-) = L(\omega^-)^+ + L(\omega^-)^-.$$ Then the block decomposition of $L$ is simply $$L = \begin{pmatrix} A & B \\ C & D \end{pmatrix},$$ $$A(\omega^+) = L(\omega^+)^+, \quad B(\omega^-) = L(\omega^-)^+,$$ $$C(\omega^+) = L(\omega^+)^-, \quad D(\omega^-) = L(\omega^-)^-.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.